Jurisprudence as a Manifestation of Legal Findings by Judges in Civil Cases That Embodies Principles of Justice and Certainty - Pujiningsih, Diana (Faculty of Law, Universitas Pekalongan, 2024)
A legislative regulation as the basis of legal legality within the Rechtsstaat tradition has its own limitations. Legislation never fully and in detail regulates how legal rules should be applied in every legal event; therefore, jurisprudence serves to complement it. In addition to filling legal gaps, jurisprudence is a legal instrument aimed at upholding justice and legal certainty.This research seeks to answer the question of how jurisprudence exists as a result of legal findings by judges that ensures justice and legal certainty. Based on Article 24 of the 1945 Constitution, which is further elaborated in Article 1, point 1 of Law No. 48 of 2009 on Judicial Power, judges are granted the authority to interpret or reason legally. Moreover, when laws are incomplete or unclear, judges must engage in legal findings (rechtsvinding).In relation to this, referring to Article 24 of the 1945 Constitution, and further explained in Article 1, point 1 of Law No. 48 of 2009 on Judicial Power, judges are given the authority to interpret or reason legally. In addition, when the law is incomplete or unclear, judges are required to engage in legal findings (rechtsvinding). When the content of a legislative regulation is unclear, judges are obligated to interpret it in such a way that a truly fair decision can be reached, aligning with the intent of the law, which is to achieve legal certainty.